2020
DOI: 10.1007/s41669-020-00211-0
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Monetary Valuation of a Quality-Adjusted Life-Year in the Kingdom of Saudi Arabia: A Willingness-to-Pay Analysis

Abstract: Background No willingness-to-pay (WTP) per quality-adjusted life-year (QALY) value exists for the Kingdom of Saudi Arabia (KSA). Objective The primary objective of this study was to determine the WTP for a QALY in the KSA. Methods Adult citizens of the KSA, patients with cancer, or members of the general public (MGP) were recruited to participate in a time trade-off survey to elicit health utilities. Cancer was chosen as the disease of interest for patients and the MGP, with a scenario describing stage 3 color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Demographic and work characteristics. Based on recent studies and theoretical considerations, 5,8,13 data were collected about the demographic characteristics of the school workers, including gender, age, marital status, profession, educational level, monthly income, number of dependants, private insurance ownership and incidence of chronic disease. The independent variables are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic and work characteristics. Based on recent studies and theoretical considerations, 5,8,13 data were collected about the demographic characteristics of the school workers, including gender, age, marital status, profession, educational level, monthly income, number of dependants, private insurance ownership and incidence of chronic disease. The independent variables are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…4 A limited number of studies has investigated willingness to pay (WTP) for health insurance in KSA. [5][6][7][8] Furthermore, none of these studies assessed employment-based health insurance. Therefore, this is the first study on the feasibility and acceptability of health care financing reform in the KSA, specifically the willingness of the public school workers to participate in employment-based health insurance and to investigate the WTP of those who were willing to participate.…”
Section: Introductionmentioning
confidence: 99%
“…The first publication of the willingness-to-pay (WTP) threshold for the KSA was done by Bazarbashi et al, 39 who proposed a country estimate of US $25,600 and $32,000 from the demand-side approach that represents societal WTP. The proposed threshold provided in this analysis is close to the lower range of the WHO CHOICE recommendations (1 times the GDP per capita).…”
Section: Discussionmentioning
confidence: 99%
“…Out of the four CV studies, the study that elicited the highest WTP ($589,822) for a QALY was a study conducted among the general population in Sweden that elicited their WTP for an insurance scheme that provided access to a drug that would prolong their lives if they were diagnosed with cancer for the next 10 years [45]. Another study in Saudi Arabia reported an OOP WTP of $32,142 to move from a state of stage 3 colorectal cancer to perfect health among 378 respondents who were either cancer patients or general population [46]. In Thailand, the OOP WTP of 300 respondents to move between different health states of lung cancer was between − $4,973 to $46,039 for patients and − $2452 to $71,642 for general population [47].…”
Section: Wtp Outcomes Reportedmentioning
confidence: 99%
“…For studies using CV method, only 3/24 (12.5%) studies [45,61,66] were considered of high quality, 13/24 (54.2%) were of moderate quality [46,55,58,59,62,64,68,71,73,76,[79][80][81], and 8/24 (33.3%) [47,54,56,60,63,67,70,77] were of low quality. Majority of the CV studies lacked information on test for validity and reliability, with only 50% and 16.7% of the studies reporting on validity and reliability test, respectively.…”
Section: Quality Assessmentmentioning
confidence: 99%